2009
DOI: 10.1021/ja901448d
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Acid Amplifiers for EUV Lithography

Abstract: Five new compounds were synthesized for use as acid amplifiers in EUV (13.5 nm) photoresists. Four compounds act as acid amplifiers and decompose by autocatalytic kinetics to generate fluorinated sulfonic acids, essential for the simultaneous improvement of resolution, sensitivity, and line edge roughness (LER) in EUV photoresists. The decomposition rates were studied using (19)F NMR in the presence and absence of 1.2 equiv of tri-tert-butylpyridine. Three acid amplifiers decomposed 490, 1360, and 1430 times f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 12 publications
(16 reference statements)
1
39
0
Order By: Relevance
“…The use of acid amplifiers to increase acid generation by orders of magnitude has been suggested [33] but not been applied to HVM. Recently, the application of acid amplification to EUV CARs was proposed [34]. An EUV resist loaded with an acid amplifier showed 25% higher sensitivity than the original formulation [35].…”
Section: Sensitivity Enhancement Methodsmentioning
confidence: 99%
“…The use of acid amplifiers to increase acid generation by orders of magnitude has been suggested [33] but not been applied to HVM. Recently, the application of acid amplification to EUV CARs was proposed [34]. An EUV resist loaded with an acid amplifier showed 25% higher sensitivity than the original formulation [35].…”
Section: Sensitivity Enhancement Methodsmentioning
confidence: 99%
“…Product analysis experiments 14 showed that the pathways for the unwanted, noncatalytic decomposition reactions involved either S N 2 or S N 1 reactions between phenolic nucleophiles in polymer films or in solution and the primary sulfonic ester bonds ( Figure 4). We, therefore, devised a strategy for blocking both decomposition pathways by preparing acid amplifiers with a trifluoromethyl (-CF 3 ) group alpha to the sulfonic ester.…”
Section: 1mentioning
confidence: 99%
“…Combining both the olefin trigger and the fluorinestabilized capacity into one trigger-body design, we produced acid amplifiers AA4 and AA5 ( Figure 5), which are designed to produce pentafluorobenzene-sulfonic acid (C 6 F 5 SO 3 H, PFBS) and triflic acid (CF 3 SO 3 H, TfOH), respectively. Using some of our original body-trigger designs, [14][15][16][17][18] we have been able to prepare AAs that generate PFBS, but, until now, we have never been able to prepare stable AAs that make acids any stronger than PFBS acid. Using the olefin/-CF 3 design, not only have we been able to prepare AAs that generate PFBS, but for the first time, we are able to prepare an AA that generates TfOH…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Our approch is a logical extension of our group's design of acid amplifiers [10][11][12][13], in which specifically-designed blocking groups protect sulfonic acids. In DD-CAMP, however, our specially-designed blocking groups protect polymer-bound carboxylic acids that provide the solubility switches in these positive-tone resists.…”
Section: Introductionmentioning
confidence: 99%